2021
DOI: 10.1017/dmp.2021.42
|View full text |Cite
|
Sign up to set email alerts
|

Psychosis, Telehealth, and COVID-19: Successes and Lessons Learned From the First Wave of the Pandemic

Abstract: Objective: This brief report analyzes a first-episode psychosis (FEP) clinic’s shift from in-person treatment to the provision of services through telemental health during the COVID-19 pandemic. The feasibility of using this technology was examined by assessing client engagement. Methods: The authors created and implemented procedures for the clinic’s transition to telemental health. Once clients’ consent was obtained, a HIPAA compliant platform was used to continue service provision. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 5 publications
0
7
1
Order By: Relevance
“…While our study showed an increase in service activity which may in part be explained by improved service access, there was a higher percentage of missed appointments. This differs from previous studies which suggest that with telepsychiatry, clients are more likely to keep appointments and it may increase attendance rates by improving accessibility to services (Chaudhry et al, 2021 ; Leigh et al, 2009 ).…”
Section: Discussioncontrasting
confidence: 84%
See 2 more Smart Citations
“…While our study showed an increase in service activity which may in part be explained by improved service access, there was a higher percentage of missed appointments. This differs from previous studies which suggest that with telepsychiatry, clients are more likely to keep appointments and it may increase attendance rates by improving accessibility to services (Chaudhry et al, 2021 ; Leigh et al, 2009 ).…”
Section: Discussioncontrasting
confidence: 84%
“…Some studies suggest that telepsychiatry may increase attendance rates by improving accessibility to services and removing barriers to travel (Chaudhry et al, 2021 ; Leigh et al, 2009 ). Several challenges to implementation however have been raised, including technological challenges and maintaining privacy and confidentiality, while carrying out clinical assessments and treatment (Zhang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These perspectives may have now shifted as patients and families become more comfortable with virtual care as a feasible service delivery method 44 , especially for those who may not feel comfortable leaving the house, experience stigma coming to a hospital, or do not live close to services, all of which emerged as top barriers to engagement in the surveys. Virtual care has the potential to make appointments more flexible and maintain or improve appointment attendance [44][45][46] , but it is not a one-size-fits-all approach; a blended treatment model may benefit patients at different points in their care journey, though more highquality trials are needed to examine the clinical effectiveness of virtual and blended models of care 47 .…”
Section: Discussionmentioning
confidence: 99%
“…The limit of telehealth is the inability for the clinician to rate some symptoms like antipsychotic-induced extrapyramidal symptoms or to carry out a neurological clinical examination. An hybrid model of in-present and telehealth, therefore, appears to be a good option to improve the performance of psychiatric care for both patients and healthcare professionals [23,[39][40][41][42][43].…”
Section: Key Pointsmentioning
confidence: 99%